Degradation of Perfluorooctane Sulfonamide by Acinetobacter Sp. M and Its Extracellular Enzymes. Issue 16 (16th July 2019) - Hao, Jian; Wang, Penghong; Kang, Yufei; He, Haitao; Luo, Huihua; Kim, Sarah; Niu, Lili; Jiang, Haizhen; Ma, Kesen
Abstract: The Acinetobacter sp. strain M isolated from a contaminated soil sample in Jiangsu Province of China was found to be able to degrade perfluorooctane sulfonamide (PFOSA) effectively. Fluoride anion (F − ) released from PFOSA degradation was detected by ion chromatography, and showed positive correlation to the growth curve of Acinetobacter sp. strain M. The PFOSA degradation efficiency of strain M was approximately 27 %, as assessed by GC analysis. It was shown that enzymes localized outside of cells of Acinetobacter sp. strain M catalyzed the degradation of PFOSA. This further indicates a possibly new (multi‐step/pathway) mechanism for PFOSA degradation. It revealed that the extracellular enzyme of the Acinetobacter strain M preferentially cleaves carbon‐carbon and carbon‐fluorine bonds instead of destroying the carbon‐sulfur bond. The growth condition for Acinetobacter sp. strain M was optimized at 30 °C and pH 7.0 in the presence of 2000 mg L −1 of PFOSA and 0.5 % (v/v) of Tween‐20. The optimal PFOSA degradation time was found to be 12 h, with a degradation efficiency of 76 % by extracellular enzymes in strain M as determined by GC analysis. The result may provide potential applications for biodegradition of perfluoro organic compounds, such as derivatives of perfluorooctane (C8). Abstract : Being degrading : The Acinetobacter sp. strain M isolated from a contaminated soil sample was found to be able to degrade perfluorooctane sulfonamide (PFOSA) effectively. Fluoride anion released from PFOSA degradation was detected by ion chromatography, and showed positive correlation to the growth curve of Acinetobacter sp. strain M. It was shown that enzymes localized outside of cells of Acinetobacter sp. strain M catalyzed the degradation of PFOSA. This further indicates a possibly new (multistep/pathway) mechanism for PFOSA degradation.